(untitled) (Fiep Bulletin - online, 2014)
The aim of this study was to demonstrate the need for knowledge of struggles for physical education classes at school. Thus, were compared the knowledge of pupils of the sixth and third periods of the degree course in physical education about content of struggles in the school context UNIABEU, in other words, students who had (sixth semester) and who have not had (third semester) discipline of teaching methodology of fights. The sample was 37 students of both genders, including 17 students from sixth period and 19 from third period. Data were collected through a semi-structured questionnaire, consisting of 10 questions, adapted from the questionnaire developed by FERREIRA (2009). The results showed significant differences at two items assessed: (i) correct definition of struggles according to the Parâmetros Curriculares Nacionais (p = 0,01824) and (ii) the possibility of giving lessons in school with students of both sexes (p = 0,03582). So, our results demonstrated that while most students feel able to minister classes struggles in school physical education classes, many students who have not had the disciplinary content methodology in fights at graduation, although they already had practiced or still practice some form of struggle, do not have correct concepts about struggles and still do not know how to work correctly fights in the school context.